The Role of Self-Regulated Motivation in Fostering EFL Learners’ Academic Writing Skills - Kristian Florensio Wijaya; Marshinel Shiwani Nelson; Jade Jatuporn (Universitas PGRI Semarang, 2025)
This study highlights the importance of fostering strong self-regulated motivation in EFL learners before engaging them in complex academic writing tasks. Drawing from educational psychology, it emphasizes how motivation plays a key role in navigating the challenges of academic writing. This small-scale library research aimed to explore how self-regulated motivation supports the development of academic writing skills among EFL learners. Through thematic analysis of 25 relevant studies, the research identified two key findings: (1) self-regulated motivation helps EFL learners become more organized in their writing process, and (2) it contributes to better academic writing outcomes. Overall, the study reinforces the need for educators to prioritize motivation in academic writing instruction.